Dynamic Modeling and Damping Function of GUPFC in Multi-Machine Power System - Hadi, Sasongko Pramono (IPTEK The Journal for Technology and Science, 2011)
This paper presents a new dynamic model of multi-machine power system equipped with GUPFC for power system study, and using PSS and GUPFC POD controller some effective control schemes are proposed to improve power system stability. Based on UPFC configuration, an additional series boosting transformer is considered to define a GUPFC configuration and its mathematical model; Phillips-Heffron scheme is used to formulate machine model, and modification of network dealing with GUPFC parameter is carried out to develop a MIMO as well as comprehensive power system with GUPFC model. Genetics Algorithm method was proposed to lead-lag compensation design, this technique provides the parameter controller. The controller produced supplementary signals, the PSS for machine and POD for GUPFC. By applying a small disturbance, the dynamic stability power system was investigated. Simulation results show that the proposed power system with GUPFC model is valid and suitable for stability analysis. The installation of GUPFC without POD decreased the damping oscillation. But, the results show that the presence of GUPFC in power system network provided by PSS and POD controller is very potential to improve system stability. A 66% overshoot reduction could be reached, it is obtained 12 s in settling time (shorter), although the rise time become 700 ms longer. Simulation results revealed that the role of POD controller is more dominant than the PSS, however both PSS and GUPFC POD controller simultaneously present a positive interaction. Phase angle of converter C, Î´C is the most significant control signal POD in oscillation damping.